2021
DOI: 10.3390/polym13050731
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fire Protection Performance and Mechanical Properties of Thin-Ply Bio-Epoxy Composites

Abstract: Hybrid composites composed of bio-based thin-ply carbon fibre prepreg and flame-retardant mats (E20MI) have been produced to investigate the effects of laminate design on their fire protection performance and mechanical properties. These flame-retardant mats rely primarily on expandable graphite, mineral wool and glass fibre to generate a thermal barrier that releases incombustible gasses and protects the underlying material. A flame retardant (FR) mat is incorporated into the carbon fibre bio-based polymeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It has been reported that in particleboards produced by adding 10, 20, and 30% stone wool using urea formaldehyde glue, the mineral wool reduced the bending strength by up to 65% and the internal bond strength by up to 71%, due to the reduction of the cohesion force inside the board (Mamiński et al 2011;Yap et al 2021). Cong et al (2021) added a layer of mineral wool and glass wool to epoxy-based carbon fiber polymeric laminates and investigated their combustion and mechanical properties. Results indicated that the addition of the flame-retardant layers reduced the bending strength from 836.4 to 767.0 MPa.…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 99%
“…It has been reported that in particleboards produced by adding 10, 20, and 30% stone wool using urea formaldehyde glue, the mineral wool reduced the bending strength by up to 65% and the internal bond strength by up to 71%, due to the reduction of the cohesion force inside the board (Mamiński et al 2011;Yap et al 2021). Cong et al (2021) added a layer of mineral wool and glass wool to epoxy-based carbon fiber polymeric laminates and investigated their combustion and mechanical properties. Results indicated that the addition of the flame-retardant layers reduced the bending strength from 836.4 to 767.0 MPa.…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 99%
“…Some of the systems reported in Table 4 used epoxy resins or magnesium hydroxide particles for the preparation of flame-retardant coatings. Cong et al [50] prepared hybrid composites of bio-based thin-ply carbon fiber prepreg and flame-retardant mats (E20MI). The inclusion of FR mats in the thin-ply bio-based prepreg revealed that the FR mat location can increase both the fire protection results and the mechanical properties.…”
Section: Fire Test Resultsmentioning
confidence: 99%
“…For instance, Li et al 15 designed an intumescent flame-retardant mat for CF-reinforced composites and reported a reduction in the heat release rate with side effects on mechanical properties and extra smoke emission. Cong et al 16 confirmed this issue and proposed that the poor structural stability of the surface protection layer leads to the deterioration of the mechanical properties of the composites. Nonetheless, it remains unclear what strategy to use to balance between fire resistance and structural performance for high-performance fiber-reinforced composites.…”
mentioning
confidence: 95%
“…Cong et al. 16 confirmed this issue and proposed that the poor structural stability of the surface protection layer leads to the deterioration of the mechanical properties of the composites. Nonetheless, it remains unclear what strategy to use to balance between fire resistance and structural performance for high-performance fiber-reinforced composites.…”
mentioning
confidence: 95%